2011
DOI: 10.1007/s11104-011-0967-8
|View full text |Cite
|
Sign up to set email alerts
|

Origin of mound-field landscapes: a multi-proxy approach combining contemporary vegetation, carbon stable isotopes and phytoliths

Abstract: Background and aims Seasonally flooded South American savannas harbor different kinds of mound-field landscapes of largely unknown origin. A recent study used soil carbon-isotope depth profiles and other proxies to infer vegetation history in murundu landscapes in Brazil. Results suggested that differential erosion, not building-up processes (e.g., termite mounds), produced mounds. We tested this approach to inferring mound origin in a mound-field landscape in French Guiana. Methods We examined carbon-isotope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
1
13
0
3
Order By: Relevance
“…Los ejemplos de montículos naturales y antrópicos son numerosos en América del Sur, implicando diferentes ingenieros naturales como las hormigas, las termitas, las lombrices de tierra o aún las plantas, hasta fenómenos físico-químicos (RENARD et al, 2012;MCKEY et al, 2014). Podemos analizar dos casos particularmente interesantes de co-construcción de esos paisajes por humanos y por ingenieros animales entre otros las hormigas.…”
Section: Montículos Naturales En Zonas Inundablesunclassified
“…Los ejemplos de montículos naturales y antrópicos son numerosos en América del Sur, implicando diferentes ingenieros naturales como las hormigas, las termitas, las lombrices de tierra o aún las plantas, hasta fenómenos físico-químicos (RENARD et al, 2012;MCKEY et al, 2014). Podemos analizar dos casos particularmente interesantes de co-construcción de esos paisajes por humanos y por ingenieros animales entre otros las hormigas.…”
Section: Montículos Naturales En Zonas Inundablesunclassified
“…The mounds are piles of soil or a type of micro relief in landscapes associated with poor drainage conditions (Resende et al, 2002). Their origin remains controversial (Renard et al, 2012) with two competing hypotheses (Silva et al, 2010) -a termite mound origin versus differential erosion over time. The termite mound hypothesis suggests successful colonization by successive generations of termites that thereby increases the diameter and height of these structures, which are further acted upon by earthworms and ants (Resende et al, 2002).…”
Section: Research Article -Antsmentioning
confidence: 99%
“…In recent years, much research has been conducted on the relationship between the δ 13 C value, climate, habitat conditions, and the soil water content. The main trend observed is a higher δ 13 C value as the availability of resources decreases [8][9][10][11][12]. However, no research has been reported on the δ 13 C value and the WUE of plant species from different lithologic habitats in karst areas.…”
Section: Introductionmentioning
confidence: 99%